2019
DOI: 10.5603/ocp.2018.0051
|View full text |Cite
|
Sign up to set email alerts
|

Advances in systemic treatment of advanced soft tissue sarcomas

Abstract: Systemic treatment in soft tissue sarcoma (STS) is an important element of therapy in a disease eligible for combined treatment with a radical intention and is the basis for the treatment of an unresectable or metastatic disease. The possibilities of treating STS are limited and for many years progress in this area was minor and the main drugs used in this indication were and still remain anthracyclines and alkylating agents. Clinical trials with new drugs are difficult for STS due to the heterogeneity of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Most recently, tazemetostat showed activity in advanced ES with loss of INI1/SMARCB1. Tazemetostat therapy is a new treatment option for patients with ES approved by the FDA [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, tazemetostat showed activity in advanced ES with loss of INI1/SMARCB1. Tazemetostat therapy is a new treatment option for patients with ES approved by the FDA [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…The ENLIVEN study published in 2016 demonstrated that oral doses of pexidartinib (inhibitor of the colony stimulating factor 1 receptor, CSF1R) is effective in treating GCTTS. It is noteworthy that this study included only patients above 18 years of age and at this moment there are no published articles regarding its use in the pediatric population [12,14,[23][24].…”
Section: Mostmentioning
confidence: 99%
“…The global incidence rate of GCTTS located in the digits, limb and the diffuse-type are respectively 29, 10, and 4 per million person-years [11]. GCTTS is even less common in the pediatric population, with an incidence rate of 2.42 and 1.09 per million person-years in case of localized and diffuse tumors, respectively [12]. The knowledge about pediatric GCTTS is scattered across case reports and case series [7,13].…”
Section: Introductionmentioning
confidence: 99%